Antifeedant Activity from Leaves Extract of Aglaia ganggo Miq on Spodoptera litura - Purwatiningsih Purwatiningsih; I Nyoman Adi Winata (Jurnal ILMU DASAR, 2013)
The different fraction extracts (viz methanol, dichlorometana, n-hexane, ethylacetate, and aceton) obtained from leaves of Aglaia ganggo Miq were investigated for antifeedant activity against Spodoptera litura. All extract fractions showed antifeedant activity with aceton fraction exhibited the highest antifeedant activity at 1 ppm concentration. Only hexane fraction showed a dose dependent concentration while the other fractions exhibited the opposite respond.Keywords : Antifeedant, Aglaia ganggo, extract, fraction